JEH Acceptance Letter 29 Sept 2014 - Cisneros, Kristen (My University, 2014)
Letter of acceptance for publication of "PM2.5 Airborne Particulates Near Frac Sand Operations" in the November 2015 issue of the Journal of Environmental Health (http://www.neha.org/JEH/).